Peran Keberadaan Sirkuit Mandalika Terhadap Ekonomi Masyarakat di Dusun Sade, Lombok Tengah - Riska Riska; Prayitno Basuki; Irwan Suriadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of the Mandalika Circuit in the economic conditions of the Sade Hamlet community in Central Lombok, a cultural tourism village located in the Mandalika buffer zone. This study used a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Informants included the Central Lombok Tourism Office, the Head of Sade Hamlet, the Tourism Awareness Group (Pokdarwis), tour guides, weavers, souvenir vendors, and community leaders. The research results show that the Mandalika Circuit plays a role in improving the economy of the Sade Hamlet community. Increased tourist visits during international events directly contribute to increased household income, particularly through tour guide services, the sale of woven crafts, the souvenir trade, and cultural performances. Job diversification from agriculture to tourism is increasingly evident, especially among the productive age group. However, this study also identified several obstacles, such as limited foreign language skills, the unpreparedness of some business owners to manage increasing tourism demand, increasingly fierce business competition, and the challenge of maintaining cultural authenticity amidst the commercialization of tourism.